Financial Sector Assessment : Montegnegro - World Bank; International Monetary Fund (World Bank, Washington, DC, 2016)
The Montenegrin economy has yet to recover from the collapse of the lending boom in 2008. The financial crisis hit asset quality, weakening banks’ portfolios. The legacy of pre-crisis rapid increase in indebtedness is adding to banking sector vulnerabilities. The crisis triggered a prolonged period of balance sheet deleveraging, which has translated into a near uninterrupted credit contraction. Slow economic growth and gaps in the legal framework have hampered banks’ efforts to reduce the overhang of nonperforming loans (NPLs). The CBM-managed payment and settlement systems are generally efficient. Some adjustments are needed to minimize any residual liquidity risks, such as facilitating the automatic transfer of balances from the reserves account to the settlement account. The CBM oversight function should be strengthened through the formulation of an oversight policy framework along with improvements to interdepartmental communication and exchange of information. The growth of the financial sector has contributed to greater access to finance for individuals and SMEs, but a number of weaknesses in the regulatory and enabling environment need to be addressed.